Pengaruh Jenis Perekat pada Briket dari Kulit Buah Bintaro terhadap Waktu Bakar - Erlinda Ningsih; Yustia Wulandari Mirzayanti; Henny Silvia Himawan; Helvi Marita Indriani (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Bintaro fruit is a plant that thrives in the tropics and has a fruit content of lignocellulose fibers bintaro potential as raw material briquettes. The purpose of this study was to examine the effect of various types of adhesives are tapioca, sago, lacquers and latex to time in the manufacture of fuel briquettes from the rind bintaro. Briquetting is carried out with a composition of 80% charcoal briquettes and type of adhesive respectively 20%. The results showed that the briquettes from the skin bintaro complies with SNI where the addition of starch adhesive obtained the best conditions, the water content of 1.91%, ash content of 7.35%, 15.34% levels of substance evaporates, 72 minute burn time and value kalornya 6000.46 calories / gram